BEYOND MEMORIZATION: TRANSFORMING ISLAMIC RELIGIOUS EDUCATION THROUGH DEEP LEARNING IN INDONESIAN BORDER-AREA SCHOOLS - Riswadi Riswadi; Zen Amrullah; Wahdatun Nisa; Mubarak Mubarak; Muhammad Sali (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aims to examine how a deep learning approach transforms Islamic Religious Education beyond memorization toward meaningful understanding and value internalization in Indonesian border-area schools. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with teachers, school leaders, and students, and analysis of instructional documents. The data were analyzed thematically to identify patterns of pedagogical change and value formation. The findings reveal that deep learning shifts Islamic Religious Education from surface-level content transmission to reflective, contextual, and dialogical meaning-making. Teachers’ roles evolve from knowledge transmitters to facilitators of inquiry and reflection, while students demonstrate greater engagement, critical thinking, and a deeper connection to Islamic values. The integration of students’ lived religious experiences strengthens the internalization of moral and spiritual values. The study implies that deep learning provides a transformative pedagogical framework for Islamic Religious Education, particularly in culturally diverse and peripheral contexts. It contributes to the theoretical expansion of deep learning discourse into faith-based education and offers practical guidance for developing reflective, student-centred Islamic Religious Education instruction.